System dynamics modeling for the land transportation system in a port city. (June 2014) - Yu, Bin; Zhang, Chao; Kong, Lu; Bao, Hong-Li; Wang, Wen-Si; Ke, Shuiping; Ning, Guobao
Land transportation systems in a port city could contribute to the competitiveness of the port and the economic development of the city. However, in port cities the land transportation system, which includes many interrelated factors, is complex. A system dynamics approach was applied to analyze the land transportation system, which was divided into economy, transport network and transportation investment subsystems. Then, system dynamics models were built to simulate the interactive relationship between the land transportation system in a port city and the economy in the port. The proposed system dynamics models analyze the impact of different transportation levels and the proportion of road and railway investment on the land transportation systems in a port city. Finally, the research takes Tianjin city as an example for numerical analysis, and analyzes the impact of different combinations of transport investment on the land transportation system in a port city.